A multifunctional hydrogel and its preparation method and application
By developing a multifunctional hydrogel loaded with black scale nanosheets, it uses its adhesion and antibacterial properties to solve the problems of caries eradication and dental surface repair in early caries treatment, and achieves effective protection of teeth and Remineralization avoids the side effects of traditional methods.
Patent Information
- Application Number
- CN202411381750.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-07
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The prior art is difficult to achieve simultaneously eradication of caries bacteria and repair of dental demineralization in early caries treatment, and common antibiotics and fluorine preparations have side effects, such as tooth coloring, multidrug resistance and fluoride dental disease. .
Develop a multifunctional hydrogel with a carrier including catechol modified chitosan CHI-CS and PLGA-PEG-PLGA, physically loaded black scale nanosheets, prepared by EDC/NHS coupling reaction to form BP@ CP5 hydrogel has excellent fluidity, adhesion and antibacterial properties.
BP@CP5 hydrogel can effectively sterilize and long-acting antibacterial, provide calcium source for remineralization, and has good biocompatibility and safety. It is suitable as a management drug for early caries.
Smart Images

Figure CN118873415B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogels, and in particular to a multifunctional hydrogel and a preparation method and application thereof. Background Art
[0002] Dental caries is a chronic disease that is prevalent worldwide. So far, about 2.44 billion people suffer from permanent dental caries. Due to its wide range of impact, high incidence, and the fact that early symptoms are easily ignored, dental caries has become a public health problem that needs to be urgently addressed. Early dental caries is the initial stage of dental caries development, which is mainly manifested by changes in enamel structure. Clinically, dental white spots or shallow dental cavities are usually seen. If effective prevention and control measures are not taken at this stage, dental caries bacteria will continue to produce acid on the tooth surface, leading to the formation of dental Ca. 2+ The tooth decay progresses to this extent, and eventually leads to tooth disintegration and substantial defects. Once caries develops to this extent, the infected tooth tissue needs to be removed and repaired and replaced with artificial materials. Although this method can repair the defects, artificial materials cannot be compared with natural teeth in terms of function and aesthetics, and the occurrence of complications will also bring a series of health and economic problems. Therefore, the effective prevention and treatment of early caries is extremely important for maintaining oral health.
[0003] Given that the cause of early caries is the colonization of a large number of cariogenic bacteria on the tooth surface, which leads to demineralization and structural disintegration of tooth tissue, the treatment of early caries must not only eradicate cariogenic bacteria but also repair the demineralized tooth surface to maintain the integrity of the tooth structure. Currently, antibiotics such as chlorhexidine and triclosan are often used clinically to eradicate cariogenic bacteria, and fluoride preparations are used to prevent demineralization of the tooth surface. However, these treatment methods still have many limitations. For example, the long-term use of chlorhexidine and triclosan may not only cause tooth staining, but also induce multidrug resistance of oral bacteria, oral flora imbalance, and even have potential effects on systemic health. In addition, although fluoride preparations such as fluoride protective varnish and fluoride foam can enhance the acid resistance of teeth, the excessive accumulation of fluoride ions in the body can easily cause diseases such as fluorosis and skeletal fluorosis; therefore, it is urgent to develop some materials that have both antibacterial and remineralization properties for efficient caries prevention. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a multifunctional hydrogel and a preparation method and application thereof to solve the above problems.
[0005] The technical solution of the present invention is achieved as follows: a multifunctional hydrogel comprises a carrier, and the carrier comprises:
[0006] Catechol-modified chitosan CHI-CS;
[0007] PLGA-PEG-PLGA hydrogel;
[0008] Among them, black-scale nanosheets BPNs are physically loaded on the carrier.
[0009] Furthermore, a method for preparing a multifunctional hydrogel comprises the following steps:
[0010] S1. Prepare BPNs by liquid stripping and seal them for storage;
[0011] S2, coupling catechol to chitosan skeleton through EDC / NHS coupling reaction to obtain catechol chitosan CHI-CS, which was freeze-dried for storage;
[0012] S3. BPNs were mixed with CHI-CS and PLGA-PEG-PLGA to form BP@CP5 hydrogel.
[0013] Furthermore, the specific preparation steps of S1 are:
[0014] Take the black scale powder, add it to the NMP solution at a concentration of 0.2 mg / ml, then ultrasonicate it with an ultrasonic cell crusher probe for 1 h in an ice bath, and then ultrasonicate it with an ultrasonic cleaner for 20 min, repeating 9 times to obtain a mixed solution;
[0015] The mixed solution was centrifuged at 4000 rpm for 5 min;
[0016] c. After centrifugation, let the layers stand and separate. Then vacuum out the supernatant and centrifuge at 13500 rpm for 10 min. Then resuspend and wash with anhydrous ethanol. Finally, aggregate the precipitate and resuspend. Store the final dispersion at 4 °C and seal it.
[0017] Furthermore, the specific preparation steps of S2 are:
[0018] d. Take 504.2 mg of chitosan CS and fully dissolve it in 5 ml of hydrochloric acid solution, the concentration of hydrochloric acid is 1 mol / L;
[0019] e. Then, 49 mL of deionized water was added and the pH value was adjusted to 5 to obtain a mixed solution;
[0020] f. Dissolve 545.4 mg / l 3,4-dihydroxyphenylpropionic acid HCA in 5 mL ultrapure water with a pH value of 5, and then add the mixture to the mixed solution of step e to obtain a chitosan mixed solution;
[0021] g. Dissolve 575.1 mg 3.0 mmol EDC and 345.3 mg 3.0 mmol NHS in 50 mL of ethanol / deionized water mixture, then add dropwise to the chitosan mixture, stir vigorously at room temperature for 10 h, and keep the pH at 4.5-5.0;
[0022] h. The final sample was purified by dialysis against HCl solution at pH 5.0 (MWCO: 10,000 Da) for 3 days and finally freeze-dried for storage.
[0023] Furthermore, in step d, the deacetylation degree of chitosan CS is ≥95%.
[0024] The present invention also provides a use of the multifunctional hydrogel as described above, wherein the multifunctional hydrogel is used for preventing and treating dental caries.
[0025] The beneficial effects of the present invention are:
[0026] The present invention has successfully developed a multifunctional hydrogel material BP@CP5. The BP@CP5 hydrogel has excellent fluidity and can fully penetrate into the pits and fissures of the tooth surface. After being transformed into a gel, it forms a stable adhesion layer with the tooth surface.
[0027] Can provide sufficient calcium source for the remineralization process;
[0028] Able to achieve high-efficiency sterilization and long-lasting antibacterial effect;
[0029] It has good biocompatibility, can be naturally degraded in the body, and produces no toxic byproducts;
[0030] It is expected to become a safe and effective candidate drug for the management of early caries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0032] Figure 1 The particle size and scanning electron microscope image of BPNs in a specific embodiment of the present invention;
[0033] Figure 2 The nuclear magnetic resonance hydrogen spectrum of CHI-CS in the specific embodiment of the present invention;
[0034] Figure 3 The adhesion test results of various hydrogels according to the specific embodiments of the present invention on dental grinding discs and hydroxyapatite are shown;
[0035] Figure 4 The colony count data of hydrogels containing different concentrations of BPNs according to the specific embodiment of the present invention;
[0036] Figure 5 The scanning electron microscope images of the tooth grinding discs after different treatments according to the specific embodiments of the present invention are shown. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.
[0039] BPNs were purchased from China Science Material Experiment Co., Ltd. BPNs were prepared by improving the liquid exfoliation technique to prepare black scale nanosheets BPNs.
[0040] First, black phosphorus powder was added to the NMP solution at a concentration of about 0.2 mg / ml. Subsequently, the solution was sonicated for 1 h using an ultrasonic cell crusher probe in an ice bath, and then sonicated for 20 min using an ultrasonic cleaner, for a total of 9 cycles. The prepared solution was centrifuged at 4000 rpm for 5 min. After standing to separate the layers, the supernatant was aspirated and centrifuged at 13500 rpm for 10 min, then resuspended and washed with anhydrous ethanol, and finally the precipitate was aggregated and resuspended. The final dispersion was stored at 4 °C and sealed, and then added to the Figure 1 , the average size of BPNs is 215.9 nm, which is consistent with the results shown by SEM. Nanosheets with moderate sizes have good photothermal properties (50-500 nm);
[0041] Chitosan (CS, deacetylation degree ≥95%), N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC), and 3,4-dihydroxyhydrocinnamic acid (HCA) were provided by Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai, China), and N-hydroxysuccinimide (NHS) was provided by Solebol, USA. Catechol was coupled to the chitosan backbone using the EDC / NHS coupling reaction. Briefly, CS (504.2 mg) was fully dissolved in 5 mL (1 mol / L) hydrochloric acid solution. Then 49 mL of deionized water was added and the pH value was adjusted to 5. 3,4-Dihydroxyphenylpropionic acid (HCA) (545.4 mg / l) was dissolved in 5 mL of ultrapure water (pH = 5) and then added to the above solution. Meanwhile, EDC (575.1 mg 3.0 mmol) and NHS (345.3 mg 3.0 mmol) were dissolved in 50 mL (v:v=1:1) of ethanol / deionized water mixture. They were added dropwise to the chitosan mixture and stirred vigorously at room temperature for 10 h, with the pH maintained at 4.5-5.0. The final sample was purified by dialysis against pH 5.0 HCl solution (MWCO: 10,000 Da) for 3 days and finally freeze-dried for storage, see Figure 2 , the proton peak appearing near δ6.8-7.0 in 1H NMR belongs to the proton peak of the benzene ring, proving that CHI-CS was successfully synthesized;
[0042] PLGA-PEG-PLGA (PPP) was purchased from Shanghai Pengshuo Biotechnology. The ultrasonically exfoliated BPNs were prepared into an aqueous solution of a certain concentration, and then freeze-dried CHI-CS was added to fully dissolve it. Finally, it was mixed with PPP hydrogel in equal volumes to form BP@CP5 thermosensitive hydrogel. The final thermosensitive hydrogel system contained 20% PPP, 2.5% CS and 75 μg mL -1 BPNs. The final hydrogel was stored at 4 °C and sealed.
[0043] By adopting the above technical solution, catechol-modified chitosan gives the hydrogel a stable wet adhesion effect. As a cationic polysaccharide, chitosan not only provides a certain bactericidal effect, but also can tightly bind to the negatively charged BPNs through electrostatic adsorption, effectively stabilizing the black phosphorus in the hydrogel;
[0044] In addition, PLGA-PEG-PLGA gives the hydrogel thermosensitive properties. On the one hand, it is in a sol-like state at room temperature and is injectable. On the other hand, by adjusting the mass ratio to control its gelation temperature, it can gel at the physiological temperature of the oral cavity, making the prepared BP@CP5 have excellent fluidity and can fully penetrate into the pits and fissures of the tooth surface. After being transformed into a gel, it forms a stable adhesion layer with the tooth surface.
[0045] At the same time, some of the catechol bonds that fail to bind to the tooth surface can also effectively enrich the free Ca in saliva. 2+ , providing sufficient calcium source for the subsequent remineralization process;
[0046] The photothermal effect mediated by BPNs is highly effective in killing bacteria, while the cation provided by chitosan is long-lasting and antibacterial;
[0047] The chitosan and PPP components in the BP@CP5 hydrogel have good biocompatibility, can be naturally degraded in the body, and no toxic byproducts are produced.
[0048] Experimental Example 1:
[0049] The adhesion strength of the hydrogel to the tooth surface in a salivary environment was determined by a lap shear test.
[0050] First, the prepared bovine enamel discs were fixed on the base resin, and the surface was polished with 1000 sandpaper to make it flat. The surface was etched with acid for 30 seconds, and the excess enamel surface was sealed with nail polish, leaving a 5 mm × 5 mm square area, which was immersed in artificial saliva before use. Then, 25 μL of each group of hydrogels were coated on the surface of two enamel discs with a size of 5 × 5 mm. 2 The two enamel grinding discs were incubated at 37 °C for 5 min. The bonding strength of the hydrogel was tested using an electronic universal material testing machine (UTM2102, Shenzhen Sun Technology Co., Ltd, China). The bonding strength (kPa) was the maximum load (kN) divided by the bonding area (m 2 ) (n = 3). The above experiment was repeated using hydroxyapatite sheets.
[0051] result:
[0052] See also Figure 3 , the results showed that with the increase of CHI-CS concentration, the tensile and shear adhesion strength of the hydrogel also increased. This is mainly attributed to the increase of catechol groups in the hydrogel network, which increased the formation of ionic bonds. The tensile and shear adhesion strength of BP@CP5 were not significantly different from those of CP5, which shows that the addition of BPNs did not affect the tensile and shear adhesion strength of CP5. The tensile adhesion strength of BP@CP5 was not significantly different from that of fluorine protective varnish, but the shear lap adhesion strength was much greater than that of fluorine protective varnish. In order to further prove the reliability of the experiment and eliminate the errors caused by the preparation of dental abrasive sheets, we repeated the above experiments using standard HA sheets, such as Figure 3 As shown in the figure, the trend of the results was basically consistent with the measurement on the tooth grinding disc (all experiments were repeated 3 times).
[0053] Experimental Example 2:
[0054] The dose-dependent antibacterial activity of BPNs in BP@CP5 was evaluated using the colony counting method.
[0055] Take a single colony of S. mutans in brain heart infusion (BHI) medium and culture it in a 37 ℃ incubator for 24 hours; the bacterial concentration obtained is about 1.6X10 8 CFU / mL. The bacterial pellet was centrifuged at 5000 rpm for 5 min and resuspended in PBS solution. 100 μL BP@CP5 was added to a 2 mL test tube, and then the bacterial suspension (100 μL, 1 × 10 8 CFU mL−1), using an 808 nm laser at 1.0 W cm -2 The suspension was irradiated for 5 min. The residual bacteria were collected, graded diluted, and evenly inoculated on BHI plates. The plates were cultured at 37°C for 24 h, and the number of colonies was counted. The number of remaining bacteria was expressed as log 10 CFU / mL. Bacteria treated with PBS were used as controls.
[0056] result:
[0057] See also Figure 4 Compared with the control group, the blank gel can kill about 3 Log of bacteria. After adding different concentrations of BPNs, the antibacterial rate was improved. The 75ug / ml group can kill about 8 Log of bacteria, and 100ug / ml kills all bacteria.
[0058] Experimental Example 3:
[0059] Healthy bovine incisors without caries and cracks were selected, disinfected with 3% sodium hypochlorite, and rinsed with PBS. The labial enamel was cut with a thickness of about 2 mm, and the labial dentin was cut with a thickness of about 2 mm, and then cut into 4 slices (1.5-2 mm thick). The slices were demineralized in Blue Etch acid etchant for 60 s, and then rinsed with deionized water in an ultrasonic bath for 3 times for 2 min. Next, the tooth slices were dried and stored at 4°C before remineralization treatment. The tooth slices were placed in a 12-well plate, 2 ml of artificial saliva was added to each well, 100 ul BP@CP5 and DDW were added respectively, near-infrared light was irradiated for 5 min, and placed in a 37°C constant temperature shaker. Saliva and drug treatment were added once every 24 hours. After 7 days, the tooth slices were taken out and the morphology was observed under SEM.
[0060] result:
[0061] See also Figure 5, normal enamel presents a dense structure both on the surface and on the side, while the enamel surface after acid etching exposes the enamel column crystal structure, and obvious enamel columns can also be seen on the side (indicated by the yellow arrow). Although mineralized substances can be seen deposited on the enamel surface in the blank group after seven days of artificial saliva immersion, the outline of enamel columns can still be seen on the side (indicated by the yellow arrow), which shows that saliva alone cannot repair the enamel tissue damaged by the acid etchant. In contrast, the enamel surface of the BP@CP5 group presents a dense mineralized layer, and a new mineralized layer of about 15um can be seen on the side (indicated by the red area). This shows that BP@CP5 has a good remineralization effect and can repair demineralized enamel.
[0062] In summary, the present invention successfully developed a multifunctional hydrogel material BP@CP5, which uses catechol-modified chitosan CHI-CS and PLGA-PEG-PLGA hydrogel as carriers, and physically loads BPNs to jointly achieve multiple functions such as wet adhesion, antibacterial and remineralization. It is expected to become a safe and effective candidate drug for early dental caries management to prevent and treat early dental caries.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a multifunctional hydrogel for preventing and treating dental caries, characterized in that: The steps include: S1. Prepare BPNs by liquid stripping and seal them for storage; S2, EDC / NHS coupling reaction to couple catechol to chitosan skeleton to obtain catechol chitosan CHI-CS, which was freeze-dried for storage; S3, BPNs were mixed with CHI-CS and PLGA-PEG-PLGA to form BP@CP5 hydrogel; The specific preparation steps of S1 are as follows: a. Take the black scale powder and add it to the NMP solution at a concentration of 0.2 mg / ml. Then, ultrasonically treat it with an ultrasonic cell crusher probe for 1 hour under ice bath conditions, and then ultrasonically treat it with an ultrasonic cleaner for 20 minutes. Repeat 9 times to obtain a mixed solution. b. Centrifuge the mixed solution at 4000 rpm for 5 min; c. After centrifugation, let the layers stand and separate. Then vacuum out the supernatant and centrifuge at 13,500 rpm for 10 min. Resuspend and wash with anhydrous ethanol. Finally, aggregate the precipitate and resuspend it. Store the final dispersion at 4 °C and seal it.
2. The method for preparing a multifunctional hydrogel for preventing and treating dental caries according to claim 1, characterized in that: The specific preparation steps of S2 are: d. Take 504.2 mg of chitosan CS and fully dissolve it in 5 ml of hydrochloric acid solution, the concentration of hydrochloric acid is 1 mol / L; e. Then, 49 mL of deionized water was added and the pH value was adjusted to 5 to obtain a mixed solution; f. Dissolve 545.4 mg / l 3,4-dihydroxyphenylpropionic acid HCA in 5 mL ultrapure water with a pH value of 5, and then add the mixture to the mixed solution of step e to obtain a chitosan mixed solution; g. Dissolve 575.1 mg 3.0 mmol EDC and 345.3 mg 3.0 mmol NHS in 50 mL of ethanol / deionized water mixture, then add dropwise to the chitosan mixture, stir vigorously at room temperature for 10 h, and keep the pH at 4.5-5.0; h. The final sample was purified by dialysis against HCl solution at pH 5.0 (MWCO: 10,000 Da) for 3 days and finally freeze-dried for storage.
3. The method for preparing a multifunctional hydrogel for preventing and treating dental caries according to claim 2, characterized in that: In step d, the deacetylation degree of chitosan CS is ≥95%.
4. A multifunctional hydrogel for preventing and treating dental caries, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Chitosan-black phosphorus composite hydrogel and preparation method thereof
CN107007865A
Medicinal composition for preventing and treating dental caries and preparation method and application of medicinal composition
CN108310006A
AgNPs at CSSCS nanogel drug loading system and preparation method thereof
CN112294752A
Preparation method and application of A-PRF / BPNS / CS hydrogel
CN117258031A
Polymer composite hydrogel, preparation method thereof and tooth desensitization material
CN118320087A
